HISTOLOGY AND PATHOLOGY OF PTERYGIUM. - Rajabov Hamid Rashid o`g`li (Scholar Express Journals, 2024)
Pterygium is a common ocular surface disorder characterized by the growth of fibrovascular tissue over the cornea. This article provides a comprehensive overview of pterygium histology, including its pathogenesis, cellular components, and molecular characteristics. Understanding the histological features of pterygium is crucial for developing effective treatment strategies and improving patient outcomes.
Keywords: Pterygium; Histology; Ocular Surface Disorder; Fibrovascular Tissue